Profile of Primary Brain Tumor Patients Who Received Radiotherapy at Hasan Sadikin General Hospital Bandung in 2020-2021 - Rahmawaty, Siti Fira; Kusumadjati, Adji; Utama, Marhendra Satria (Indonesian Journal of Cancer, 2024)
Background: A brain tumor is a tumor that is most known for its dangerous progressivity. Brain tumor is classified into primary and metastatic types. One of the management for primary brain tumors is radiotherapy. This study aims to elucidate the medical profiles and Karnofsky Performance Status (KPS) of patients with primary brain tumors with radiotherapy in Hasan Sadikin General Hospital based on a hospital-based cancer registry (HCBR) in 2020-2021.Methods: This study was conducted with a descriptive method. The sampling technique was total sampling using 22 medical records of primary brain tumor patients with radiotherapy from the year 2020-2021 which were registered in HCBR at the Radiotherapy Department, Hasan Sadikin General Hospital.Results: Primary brain tumor patients with radiotherapy were mostly from the 25-34 years age group (27.3%), male gender (68.2%), with a regional origin of West Priangan (45.5%), the chief complaint was headache (45.5%), with topography presence of overlapping lesion in the brain (ICD-O code C71.8) (27.3%), histopathological type is predominantly astrocytic tumors (22.7%), majority of patients underwent subtotal resection (59.1%), adjuvant radiation therapy was mostly indicated (40.9%), with all patients using Linac external beam radiotherapy (EBRT) radiation device. Almost all patients can finish radiotherapy (95.5%). The waiting time for radiotherapy is mostly 5-6 weeks (31.8%).Conclusions: Primary brain tumor infects more men than women, with a predominant age group of 25-34 years old. Histopathological findings are mostly of the astrocystic tumor type with most chief complain being headaches. The most common treatment is subtotal resection followed by radiotherapy using EBRT Linac with a positive one-year-postradiotherapy prognosis.